Understanding the factors of information leakage through online social networking to safeguard organizational information - Abdul Molok, Nurul Nuha; Ahmad, Atif; Chang, Shanton (2010)
With the rapid escalation of the online social networking (OSN) use, there have been some high profile cases reported in the media about information leakage by employees that are detrimental to organizations. However, academic literature rarely discusses the impacts of OSN on organizations. This conceptual paper explores employees’ OSN use behaviour that leads to the disclosure of organizational information which may jeopardize the information systems (IS) security. In order to do that, the paper briefly reviews theories from criminology, psychology and sociology that are related to our study. We find that Decomposed Theory of Planned Behaviour is the most suitable theoretical model in explaining the underlying factors that drive information leakage through OSN. The understanding of these reasons facilitates our suggestion for organizations to safeguard information against this insider threat by employing information security education, training and awareness (SETA) programs for employees.